Meningkatkan Kesadaran Mahasiswi akan Pentingnya Produk Kosmetik Berlabel Halal - Sari, Arum Kumala; Mulyani, Sheila Arisonya; Arliani, Levia Niza; Gunawan, Ade; Sholihah, Ria Anisatus; Adinugraha, Hendri Hermawan (Welfare : Jurnal Pengabdian Masyarakat, 2024)
Public literacy regarding halal laws remains low, with people often relying on the halal label on packaging to determine if a product is halal. However, many products in the Indonesian market lack this label, leading to consumer confusion. This educational activity aims to enhance knowledge about selecting halal-certified cosmetic products and ensuring their safety. It targeted female students of the Faculty of Economics and Islamic Business at K.H. Abdurrahman Wahid State Islamic University Pekalongan and was conducted face-to-face using a lecture-based approach. The session took place on Tuesday, May 21, 2024, from 15:30 until completion, aiming to increase awareness and understanding of halal cosmetic products, which were previously not well known among the students. This training effectively raises awareness and knowledge about the halal status of cosmetic products, helping students make informed choices in their daily purchases.